Herbal medicinal products or preparations for neuropathic pain - Boyd, Adele (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the analgesic efficacy and effectiveness of herbal medicinal products or preparations for neuropathic pain, and the adverse events associated with its use.